Presence of KPC type carbapenemase in K. pneumoniae clinical isolates from intensive care unit patients - Armindo Perozo-Mena; Maribel Castellanos-González; Eliana Ling; Liliana Gómez; Messaria Ginestre; Gresleida Rincón (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2016)
Klebsiella pneumoniae is an important opportunist pathogen that mainly cause outbreaks in health institutions, when it acquires the ability to produce carbapenemase, becomes resistant to betalactamics and other groups of antimicrobials as quinolones and aminoglycosides. The aim of this study was to determine the presence of K. pneumoniae strains producing KPC type carbapenemase in clinical isolates of hospitalized patients from three intensive care units of a health institution. All K. pneumoniae strains isolated from routine cultures performed to patients held in the three units were studied, identification was performed by automated equipment Vitek 2C, susceptibility tests were made by Bauer -Kirby method and detection of KPC carbapenemase was done by the modified Hodge test, imipenem and meropenem MIC and blaKPC gene amplification. The results indicate a high prevalence of KPC carbapenemase in the institution, a marked pattern of multidrug resistance was observed in the KPC carbapenemase producing strains, it is recommended to carry out studies to understand the epidemiology and transmission of this resistance mechanism within the institution.